2009
DOI: 10.2151/jmsj.87.525
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model Projection of Global Warming Impact on Tropical Cyclone Genesis Frequency over the Western North Pacific

Abstract: This study examines the global warming impact on tropical cyclone (TC) genesis frequency over the western North Pacific basin (0 -40 N, 100 E-180 ; WNP) projected by five atmosphere-ocean coupled general circulation models that participate in the World Climate Research Programme's Coupled Model Intercomparison Project phase 3 (CMIP3), and exhibit high performances in simulating horizontal distribution of annual-mean frequency under the current climate condition. TC-like disturbances are detected and counted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…It is also important to examine whether SST spatial pattern variations in the past climate are associated with the delay of the Baiu withdrawal over Japan in the 20 th century revealed by previous studies (e.g., Sato and Takahashi 2001). Yokoi and Takayabu (2009) revealed that the global warming impact on tropical cyclone genesis frequency over the WNP, and showed the increasing frequency trend is recognizable especially over the central North Pacific (5°-20°N, 150°E-180°) because of the El Niño-like SST warming pattern. The increasing area locates to the southeast of CJ area, thus the southeastward displacement of convections in the present study might be consistent with the increasing frequency of tropical cyclones.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is also important to examine whether SST spatial pattern variations in the past climate are associated with the delay of the Baiu withdrawal over Japan in the 20 th century revealed by previous studies (e.g., Sato and Takahashi 2001). Yokoi and Takayabu (2009) revealed that the global warming impact on tropical cyclone genesis frequency over the WNP, and showed the increasing frequency trend is recognizable especially over the central North Pacific (5°-20°N, 150°E-180°) because of the El Niño-like SST warming pattern. The increasing area locates to the southeast of CJ area, thus the southeastward displacement of convections in the present study might be consistent with the increasing frequency of tropical cyclones.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Therefore, the threshold values of criteria for detecting simulated TCs should be more lenient than those for real TCs. Furthermore, because model specifications such as resolution and parameterization schemes are different for each model, it is necessary to optimize different threshold values of the criteria for each model in order to appropriately detect simulated TCs (e.g., Yokoi and Takayabu 2009;Murakami et al 2012). The thresholds are optimized for each model to ensure that the present-day (PD) annual mean TC number in the WNP basin matches that observed (approximately 27 per year for the period 1979̶2007).…”
Section: Detection Algorithm For Tropical Cyclonesmentioning
confidence: 99%
“…Several studies applied process-oriented performance metrics to the CMIP3 models (e.g. Yokoi and Takayabu 2009;Nishii et al 2009). Especially, Kosaka and Nakamura (2011) found that models with better reproducibility of the climatological-mean fields tend to show better reproducibility of the most dominant summertime anomaly pattern over the western North Pacific.…”
Section: Discussionmentioning
confidence: 99%